An analysis of EFL students raising awareness of learning to speak English - Maria Anjelica Kemba; Eka Wilany; Safnidar Siahaan (University of Muhammadiyah Malang, 2026)
Raising awareness is an important in English language learning, especially for EFL students, in helping develop speaking skills and learner autonomy. This study aimed to examine how awareness-raising activities can be applied by EFL students in learning speaking and to analyze students’ achievement. This study employed a qualitative descriptive approach, with a sample of one tenth-grade class at a private senior high school in Batam’ consisting of 19 students. Data were collected through questionnaires and a speaking test. The questionnaire identified students’ perceptions of awareness-raising activities based on five main indicators: Finding out about your students, Motivation, Learning strategies, Community building, and Self-monitoring. The speaking test assessed pronunciation, grammar, vocabulary, fluency, and comprehension. Questionnaire data were analyzed descriptively using percentages, while the speaking test data were analyzed using the mean, median, mode, and score distribution. The results of the questionnaire data showed that students’ learning awareness was at a moderate level, with more prominent awareness found in the self-monitoring indicator and learning style awareness. Meanwhile, the indicators of motivation, learning strategies, and social collaboration showed less stable results. Findings from the speaking test indicated that students’ English-speaking ability was in the fairly good category, with an average score of 64.00; however, some students were still at the intermediate level. Based on these findings, raising awareness plays an important role as an initial foundation in developing speaking skills and learner autonomy. Therefore, continuous pedagogical support is needed to enhance EFL speaking instruction and provide practical contributions to the education field